 # Expanding and Simplifying Algebraic Expressions

## Presentation on theme: "Expanding and Simplifying Algebraic Expressions"— Presentation transcript:

Expanding and Simplifying Algebraic Expressions
2(x + 1) + 3(x + 3) = 2x x + 9 = 5x + 11 x + x = 2x 2x - 5x = -3x

(x - 1)(4) Four groups of (x - 1)

(x - 1)(4) This is a zero model.

How can you use algebra tiles to show that
(x - 1)(4) = 2 + 4x The simplified expression is 2 + 4x or 4x + 2. How can you use algebra tiles to show that 2 + 4x is the same as 4x + 2 ?

Simplify: 2x x - 5 x - 2x 3 (x - 1) -2 (x + 2)

Simplify: x x - 5

Simplify: 1. 2x x - 5 = 6x - 2 zero

Simplify: 2. x - 2x

Simplify: = -x - 6 2. x - 2x zero

How could you get this answer without using algebra tiles?
Simplify: (x - 1) = 3x - 3 How could you get this answer without using algebra tiles?

Simplify: (x - 2) Step 1 2 (x - 2) Step 2 The opposite

How could you get this answer without using algebra tiles?
Simplify: (x - 2) = -2x + 4 2 (x - 2) -2 (x - 2) How could you get this answer without using algebra tiles?

Steps without algebra tiles
-2 (x - 2) + 3 (2x + 1) = -2x x + 3 = 4x + 7 How could you check your answer to see if it is equivalent to the original expression?